Near-field changes in the seabed and associated macrobenthic communities due to marine aggregate extraction on tidal sandbanks: A spatially explicit bio-physical approach considering geological context and extraction regimes. (1st November 2021) - Wyns, Liam; Roche, Marc; Barette, Florian; Van Lancker, Vera; Degrendele, Koen; Hostens, Kris; De Backer, Annelies
Abstract: Based on data from Multibeam Echosounders (MBES) and Van Veen grab samples, near-field effects of marine aggregate extraction by trailing suction hopper dredgers in the Belgian part of the North Sea were assessed on a decadal scale. The combined approach allowed to investigate and compare seabed and macrobenthic community characteristics for three extraction areas with similar ecological settings, but with a different geological context and each subjected to a different extraction regime. MBES measurements detected slight alterations of the seabed for areas exposed to a continuous, low extraction regime (monthly average volume = 17 to 83 × 10 3 m 3 ). However, no significant changes in sediment composition nor the macrobenthic community could be attributed to this low extraction regime. High and continuous extraction in the most intensely extracted area (monthly average volume = 164 × 10³ m³) increased surface heterogeneity and created a local depression, hereby exposing clay and gravel from the underlying geological layer. In this area, the highest environmental impact was observed, as the physical changes in the seabed triggered a shift towards a more heterogeneous, transitional macrobenthic community including opportunistic species and species typically associated with muddy sands. Together with the species already present, this resulted in a local increase in macrobenthos density, species richness and biomass. A high but periodic extraction without screening activity on the most offshore located extraction area (monthly average volume = 230 × 10³ m³, averaged for those months where extraction took place) led to a redistribution of the medium to fine sand fraction and a winnowing of coarse sediment and shell fragments. The decreased median grain size induced a shift in the macrobenthic community from a typical medium to coarse sand Hesionura elongata community towards medium to fine sand representatives of the Nephtys cirrosa community, although the overall macrobenthic density and biomass in this extraction area remained stable. Based on these results, we conclude that extraction regime and local geological context are important factors driving the near-field environmental impact of marine aggregate extraction on tidal sandbanks. Highlights: Extraction regime and local geological context determine the impact of aggregate extraction on the seabed and macrobenthos. The macrobenthic community response matched changes in the seabed and especially changes in sediment characteristics. Impact was most drastic when high continuous extraction coincided with a varying nature in local geology and sediment types. Integrating MBES data with grab sample data allows for a spatially explicit assessment of seabed integrity.